2020
DOI: 10.1177/2332858420966994
|View full text |Cite
|
Sign up to set email alerts
|

Testing Basic Assumptions Reveals When (Not) to Expect Mindset and Belonging Interventions to Succeed

Abstract: In this case study, we investigated the effectiveness of growth mindset and social belonging interventions in a college setting with large numbers of traditionally underrepresented groups (n = 1,091). In doing so, we highlight the characteristics of the students in our study that are important for determining whether we should expect such interventions to be effective for diverse higher education populations. Correlational analyses revealed no evidence that growth mindset or social belonging were barriers to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…Aforementioned, intervention researchers are moving towards understanding heterogeneity in treatment effects (McPartlan et al, 2020 ; Walton & Yeager, 2020 ; Yeager et al, 2019 ; Yeager & Dweck, 2020 ). Our study found support for the notion that positive affective engagement with the saying-is-believing exercise may be an important first step toward engagement with the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aforementioned, intervention researchers are moving towards understanding heterogeneity in treatment effects (McPartlan et al, 2020 ; Walton & Yeager, 2020 ; Yeager et al, 2019 ; Yeager & Dweck, 2020 ). Our study found support for the notion that positive affective engagement with the saying-is-believing exercise may be an important first step toward engagement with the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they have been found to change various important outcomes, such as increased grade point average (Yeager et al, 2014 ), greater career satisfaction and psychological well-being (Brady et al, 2020 ), as well as more engagement in academic-related activities (Walton & Cohen, 2007 ). However, less is known about for whom the intervention is most effective, a topic that has received much attention as debates over wise interventions have sought to move from replicability (“does it work?”) to generalizability (“for whom does it work and why?”) (McPartlan et al, 2020 ; Tipton, 2019 ; Walton & Yeager, 2020 ; Yeager et al, 2019 ; Yeager & Dweck, 2020 ). This has required explaining heterogeneity in treatment effects.…”
Section: Introductionmentioning
confidence: 99%
“…Students exhibit lesser of a growth mentality sentiment and elevated sense of belonging compared to their peers. The reasoning behind being effective mindset interventions which comprised of a belongingness among social circles which were successful despite being at peril population (McPartlan, P. 2020) [64]. These studies and the reviews above indicate that several studies have considered varied issues relevant to the present children's and youths' mindset.…”
Section: Current Status and New Related Issuesmentioning
confidence: 99%
“…Eight studies examined the effects of growth mindset interventions on first-year undergraduate students enrolled in introductory courses (Frey et al, 2018;Samuel and Warner, 2019;Hacisalihoglu et al, 2020;McCabe et al, 2020;McPartlan et al, 2020;Saraff et al, 2020;Goldstein et al, 2021;Parada and Verlhiac, 2021). One study used graduate student sample (Cheng et al, 2021).…”
Section: Study Participantsmentioning
confidence: 99%